Short range nucleon correlations studied with electron and photon probes - I.J. Douglas MacGregor (SciPost Physics Proceedings, 2020)
This paper reviews experimental research into two- and three-body nucleon-nucleon interactions, carried out by the University of Glasgow Nuclear Physics research group. A key aim of these studies has been to elucidate the role of short-range nucleon-nucleon correlations (SRC). Studies of photon-induced two- and three-nucleon emission reactions from a range of light nuclei, carried out at the 840 MeV Mainz electron microtron MAMI-B, have provided detailed information on the contributing mechanisms. More recent electron scattering studies at the 6.0 GeV Jefferson Laboratory have probed SRC at high values of Q2 and xB and suggested a connection between SRC and the EMC effect.